Upaya Guru Pendidikan Agama Islam dalam Membentuk Pendidikan Karakter Siswa di MTsN 3 Sleman Yogyakarta - Yulianika Yulianika; Muh. Wasith Achadi (Pusat Riset dan Inovasi Nasional, 2025)
Character education is a crucial aspect in shaping a generation with noble character and religious values amid the challenges of globalization and moral decline. Islamic Religious Education (PAI) teachers play a strategic role in internalizing character values through integrated learning and exemplary behavior. This study aims to describe the efforts of PAI teachers in shaping students' character education, including planning, implementation, organizational system, evaluation, and the results of its implementation. The study employed a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The results indicate that character education programs are planned through the School Curriculum, implemented collaboratively by all teachers, and evaluated through participatory meetings. Core character values such as religiosity and discipline are instilled through activities such as Qur'an memorization (tahfidz), dhuha prayer, and integration into Islamic education subjects. The transformation of student character occurs gradually and requires a sustainable process, yet it shows positive developments supported by the school environment and parental involvement. The findings imply the importance of teacher collaboration and institutional commitment in developing contextual and continuous character education models.